Let Ω s ( n ) be a completely additive function
(i.e. Ω s ( a b ) = Ω s ( a ) + Ω s ( b ) ) satisfying Ω s ( p ) = p s where p is a prime. Then n = 1 ∑ ∞ n s Ω − s ( n ) = n = 1 ∑ ∞ n s f ( n ) Find f ( 1 0 1 7 2 9 ) Note:
f is independent of s , i.e. d s d f = 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You would also have to prove that this is the only function possible, or that f(10^1729) only has one possible value (which I don't know how to).
Maybe it is safer to reduce the scope by adding that f(n) has to be an arithmetic function.
Log in to reply
n = 1 ∑ ∞ n s f ( n ) = n = 1 ∑ ∞ n s g ( n ) If f and g are two different functions independent of s. This can be proved using contradiction and convolution.
Log in to reply
Oh yeah, I forgot to think about "true for all s". I'll hide back in my cave for now. bye :p
Problem Loading...
Note Loading...
Set Loading...
First, we know n = 1 ∑ ∞ n s F ( n ) = ζ ( s ) p = p r i m e ∑ p s − 1 F ( p ) For F being a completely additive function F. proved here .
Using this we have n = 1 ∑ ∞ n s ω − s ( n ) = ζ ( s ) p = p r i m e ∑ p s − 1 p − s = ζ ( s ) p = p r i m e ∑ ( p s − 1 1 − p s 1 ) = ζ ( s ) p = p r i m e ∑ p s − 1 1 − ζ ( s ) P ( s ) By the form we used, we deduce ζ ( s ) p = p r i m e ∑ p s − 1 1 = n = 1 ∑ ∞ n s Ω 0 ( n ) and we can work out ζ ( s ) P ( s ) = n = 1 ∑ ∞ n s ω ( n ) So, f ( n ) = ( Ω 0 − ω ) ( n ) The result follows.